Morphological and molecular characterization and differentiation of selected Kappaphycus and related species in the Philippines - Montes, Humberto R. Jr (Marine Science Institute, College of Science, University of the Philippines Diliman, 2007)
Morphological and molecular data of selected Kappaphycus varieties and related species were analyzed not only to elucidate the morphological and molecular diversity but also to reveal structural patterns and phylogenetic relationships underlying this diversity.